FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PENGUNJUNG OBJEK WISATA KOTA BATU (Studi Pada Mahasiswa Aktif Fakultas Ekonomi dan Bisnis Universitas Brawijaya, Malang) - Gazalla Taufik ; Shofwan , SE.,MSi (Ilmu Ekonomi FEB - UB, 2019)
This study aims to determine whether prices, recreational facilities, accommodation facilities, and security affect the satisfaction of visitors to Batu's tourist attractions. The research method used was descriptive quantitative method with multivariate analysis which was calculated using the help of the SmartPLS 3.2.7 program. The research sample was active student at FEB Universitas Brawijaya, Malang. The sample determination uses Slovin calculations and the sampling technique used is purposive sampling. This study uses a Likert scale model. The results of this study, three variables have a significant effect on the dependent variable, but one variable does not affect visitor satisfaction. The price variable has a significant and positive effect on the satisfaction of visitors to Batu City attractions, recreation facilities variables have a significant and positive effect on the satisfaction of visitors to Batu City attractions, accommodation facilities variables have a significant and positive effect on visitor satisfaction Batu City tourism objects, and security variables have no significant effect to the satisfaction of visitors to Batu's tourist attractions. Keywords: Price, Recreation, Accommodation, Security, Satisfaction